2020
DOI: 10.1038/s41598-020-61454-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative light-induced fluorescence-digital (QLF-D) images and images of disclosed plaque for planimetric quantification of dental plaque in multibracket appliance patients

Abstract: the purpose of the present cross-sectional clinical study was to check the ability of plaque detection and quantification by QLF-D against conventional digital photographs of disclosed plaque in multibracket appliance (MB) patients. 20 patients were included according to the following criteria: (1) upper and lower jaw treated by MB appliance, (2) patients being 16 years of age or older, (3) all central and lateral incisors as well as canines in situ, (4) absence of developmental defects, carious lesions, surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
8
0
5
Order By: Relevance
“…QLF can be unreliable for disclosing tooth surfaces covered with plaque. 29 However in the study by Amaechi et al (2019) 26 , he did report that the organoselenium sealant( Denteshield TM )did have excellent retention at 12 months. Hammad et al(2016) 30 also found plaque could still form around the buccal surfaces of the teeth despite the application of an organoselenium sealant.…”
Section: Discussionmentioning
confidence: 96%
“…QLF can be unreliable for disclosing tooth surfaces covered with plaque. 29 However in the study by Amaechi et al (2019) 26 , he did report that the organoselenium sealant( Denteshield TM )did have excellent retention at 12 months. Hammad et al(2016) 30 also found plaque could still form around the buccal surfaces of the teeth despite the application of an organoselenium sealant.…”
Section: Discussionmentioning
confidence: 96%
“…Some previous studies have used fluorescence images for PPI measurements (Coulthwaite et al, 2009; Ganss et al, 2020; Klaus et al, 2020), but plaque areas were typically determined manually using drawing tools in image editing software. A previously published semi‐automated approach relied on the use of fluorescein, a pH‐sensitive fluorescent dye that is excited by ultraviolet (UV) light (Sagel et al, 2000; Klukowska et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mansoor et al (2015) proposed a semi‐automated method to detect and quantify undisclosed autofluorescent plaque using a dedicated software developed by them (Mansoor et al, 2015). The software, however, is not publicly available and the quantification of autofluorescent plaque significantly underestimates the total plaque accumulation, since not all oral bacteria exhibit autofluorescence (Ganss et al, 2020; Klaus et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Assim, estes dados demonstraram que o uso de materiais isentos de BPA para a colagem de bráquetes pode contribuir para o acúmulo mais brando de biofilme e seus desfechos nos tecidos periodontais, inferindose que a ausência de monômeros que liberam BPA possa interferir no padrão de acúmulo de biofilme. Na literatura específica há estudos apenas in vitro, associando os monômeros utilizados nos materiais de uso odontológico e a formação de biofilme dentário (Badawi et al, 2003;Faltermeier et al, 2007;Nedeljkovic et al, 2017) (Martignon et al, 2010;Rego et al, 2010;Peng et al, 2014;Jayanthi et al, 2015; Walsh e Healey 2019; Klaus et al, 2020).…”
Section: Resistência Ao Cisalhamento E íNdice De Remanescente Adesivounclassified
“…Associado a isso, a evidenciação colorimétrica do biofilme, isoladamente ou combinada com outras técnicas, pode ser considerada como uma medida motivacional e educacional aos pacientes e seu núcleo familiar (Zotti et al, 2016;Huang et al, 2018b;Fasoulas et al, 2019;Saxena e Gunjal, 2021). No entanto, há poucas pesquisas incluindo pacientes adolescentes em tratamento ortodôntico fixo e o uso de agente evidenciador de biofilme (Boyd, 1983;Peng et al, 2014;Klaus et al, 2020;Oliveira et al, 2021b).…”
Section: Resistência Ao Cisalhamento E íNdice De Remanescente Adesivounclassified